2021
DOI: 10.1007/s12035-021-02439-1
|View full text |Cite
|
Sign up to set email alerts
|

W246G Mutant ELOVL4 Impairs Synaptic Plasticity in Parallel and Climbing Fibers and Causes Motor Defects in a Rat Model of SCA34

Abstract: Spinocerebellar ataxia (SCA) is a neurodegenerative disorder characterized by ataxia and cerebellar atrophy. A number of different mutations gives rise to different types of SCA with characteristic ages of onset, symptomatology, and rates of progression. SCA type 34 (SCA34) is caused by mutations in ELOVL4 (ELOngation of Very Long-chain fatty acids 4), a fatty acid elongase essential for biosynthesis of Very Long Chain Saturated and Polyunsaturated Fatty Acids (VLC-SFA and VLC-PUFA, resp., ≥28 carbons), which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 90 publications
1
8
0
Order By: Relevance
“…Thus, it is surprising that only pontine base neurons were severely reduced, whereas other neurons were largely spared in this case. For example, the cerebellar granular layer, which was highly positive by anti-ELOVL4 antibodies in rodents in previous reports [ 30 , 40 ], was surprisingly preserved in this study. Of note, pontocerebellar fibers, which were most severely affected, showed almost no vacuoles.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Thus, it is surprising that only pontine base neurons were severely reduced, whereas other neurons were largely spared in this case. For example, the cerebellar granular layer, which was highly positive by anti-ELOVL4 antibodies in rodents in previous reports [ 30 , 40 ], was surprisingly preserved in this study. Of note, pontocerebellar fibers, which were most severely affected, showed almost no vacuoles.…”
Section: Discussionsupporting
confidence: 68%
“…Because the ELOVL5 protein is also a fatty acid elongating enzyme but has non-overlapping substrate specificity and functions as well as catalyzes elongation of shorter carbon chain (between 18 and 22) fatty acids [ 14 ], further studies are needed to explain how mutations in ELOVL4 and ELOVL5 lead to distinct spatial patterns of neurodegeneration, by analyzing elongases and lipids in the brain. A recent report indicated that a rat model of SCA34 with c.736T>G, p.W246G mutation had a motor impairment and synaptic dysfunction but without overt neurodegeneration in the cerebellar cortex [ 30 ]. This rodent model harbors significant similarities to our case and would be useful for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…We generated and characterized a Long Evans rat model of SCA34 ( 14 , 38 ) in which we knocked in the c.736T > G (p. W246G) mutation that causes SCA34 ( 31 ). Our behavioral and functional analyses revealed that homozygous W246G SCA34 rats (MUT) develop impaired synaptic plasticity, skin lesions, and reduced a- and b-wave electroretinography amplitudes without any retinal degeneration ( 14 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used the CRISPR/Cas9 gene editing method to generate a heterozygous Long-Evans rat model of the human SCA34 by knock-in of the c.736T>G, p.W246G mutation in ELOVL4 that causes human SCA34 ( 31 ) . Further details of the generation of the knock-in rat line are previously described ( 14 , 38 ). All animal experiments were performed using retinas from 12-month-old wild type (WT), heterozygous (HET), and homozygous W246G mutant (MUT) Long-Evans rats, with genotype confirmed by PCR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation